2016
DOI: 10.3390/insects7040076
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of West Nile Virus Infection on the Midgut Gene Expression of Culex pipiens quinquefasciatus Say (Diptera: Culicidae)

Abstract: The interaction of the mosquito and the invading virus is complex and can result in physiological and gene expression alterations in the insect. The association of West Nile virus (WNV) and Culex pipiens quinquefasciatus mosquitoes results in measurable changes in gene expression; 22 gene products were shown previously to have altered expression. Sequence analysis of one product, CQ G1A1, revealed 100% amino acid identity to gram negative bacteria binding proteins (CPQGBP) in Cx. p. quinquefasciatus, Aedes aeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Upregulation of antioxidant response proteins takes place upon the consumption of a blood meal [ 14 , 17 ]. Additionally, a blood meal elicits an immune response in the mosquito; however, it has been observed that if a blood meal is infected with a pathogen, there is an enhanced surge of immune effector molecules [ 18 , 19 , 20 , 21 , 22 , 23 ]. Specifically, there is a tissue-specific regulation of these effector molecules, as seen in mosquito genera such as Anopheles and Aedes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of antioxidant response proteins takes place upon the consumption of a blood meal [ 14 , 17 ]. Additionally, a blood meal elicits an immune response in the mosquito; however, it has been observed that if a blood meal is infected with a pathogen, there is an enhanced surge of immune effector molecules [ 18 , 19 , 20 , 21 , 22 , 23 ]. Specifically, there is a tissue-specific regulation of these effector molecules, as seen in mosquito genera such as Anopheles and Aedes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This activation is associated with increased oxidative activity, antimicrobial activity, as well as signaling pathways against Gram-positive bacteria [17,18] and fungi [19][20][21]. The mosquito's GNBP has been found to be related to Plasmodium [22] and arbovirus infection [23] in Anopheles gambiae [24], A. aegypti [25], and Culex pipiens quinquefasciatus [26]. GNBPB3 and GNBPB4 function as anti-DENV in A. aegypti by activating the Toll signaling pathway [27].…”
Section: Introductionmentioning
confidence: 99%